Determinan Pencegahan Kecurangan dalam Pengelolaan Alokasi Dana Desa dengan Moralitas Individu sebagai Moderasi - Desi Arang; Suyanto; Nur Anita Chandra Putri (Jurnal Literasi Akuntansi, 2026)
Purpose: This research aims to obtain empirical evidence of the influence of apparatus competence, internal control, and whistleblowing on preventing fraud in the management of village fund allocations with individual morality as a moderating variable. Method: This quantitative research used multiple regression analysis and moderated regression analysis (MRA). The sampling method used was probability sampling, with 66 village officials in Peso Hilir District, Bulungan Regency, as respondents. Finding: Officer competence and internal control negatively influence fraud prevention, while whistleblowing positively influences fraud prevention. Furthermore, the relationship between officer competence, internal control, and whistleblowing on fraud prevention is not strengthened. Novelty: The discrepancy between the results and previous research motivated researchers to re-examine the consistency of these findings regarding the influence of officer competence, internal control, and whistleblowing on fraud prevention. Furthermore, they added individual morality as a moderating variable for fraud prevention.